Elevation‐dependent effects of climate change on vegetation greenness in the high mountains of southwest China during 1982–2013. (11th October 2017) - Tao, Jian; Xu, Tongqing; Dong, Jinwei; Yu, Xiuqin; Jiang, Yanbin; Zhang, Yangjian; Huang, Ke; Zhu, Juntao; Dong, Jianxin; Xu, Yimin; Wang, Shusheng
ABSTRACT: Effects of climate change on vegetation greenness have attracted considerable attention in the context of global change; however, the dependence of such climatic effects on elevation remains poorly understood. In this study, we examine the relationship between vegetation greenness change and climate change and, in particular, characterize how this relationship changes with elevation in the high mountains of southwest China by using the remotely sensed normalized difference vegetation index (NDVI), and observed temperature and precipitation data sets for the period of 1982–2013. The results show that vegetation exhibited a greening trend (slope: 0.0008 year −1, p < 0.01) under climate warming (slope: 0.04 °C year −1, p < 0.01) and drying (slope: −2.47 mm year −1, p > 0.05). The vegetation greening and climate warming trends were stronger in the higher elevation plateaus than in the lower elevation mountains. Statistical analysis showed that temperature was the main driving factor on vegetation greening, and the driving effect was elevation‐dependent. A substantially more significant correlation between climate warming and vegetation greening was found in the higher elevation plateaus, which reveals a higher temperature sensitivity of these plateaus. In addition, a significant correlation between inter‐annual standard deviations of NDVI and precipitation during 1982–2013 was tracked over the entire study area. Abstract : Map of the high mountains of southwest China showing the elevation pattern, landform distributions (a) and different vegetation types (b). The simple hatch indicates elevation below 1000 m above sea level.